Escala de Iguales y Práctica Deportiva: validación ecuatoriana y análisis de perfiles - Vásconez-Rubio, O,; Suriá-Martínez, R,; Vicent, M. ,; García-Fernández, J.M. , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study examines (a) the validity, reliability and factorial invariance and differences in latent means according to gender of the Peers and Sport Practice scale in Ecuadorian university students; as well as (b) the existence of profiles based on the combinations of the dimensions of the mentioned scale and the possible differences in the motives for practicing sports. 597 students of the Physical Culture career participated (M = 22.08, SD = 3.33). The structure of the scale was analyzed using confirmatory procedures supporting a three-dimensional structure (Sports Practice, Social Relationship and Social Recognition) with acceptable levels of internal consistency and factorial invariance. Higher latent means were also found in girls. Latent profile analysis confirmed two profiles (low and moderate). The group with moderate scores on the Peers and Sport Practice scale obtained higher scores on all the motives for practicing physical activity.